(untitled) (Journal of Computational Intelligence and Robotics, 2024)
With the increasing sophistication of cyber threats, the integration of machine learning (ML) techniques in network security has become imperative for detecting and mitigating evolving attacks. However, the deployment of ML models in security applications has given rise to a new breed of challenges in the form of adversarial machine learning (AML). Adversarial attacks exploit vulnerabilities in ML models, compromising their effectiveness and potentially leading to security breaches. This paper provides an in-depth exploration of the challenges posed by adversarial machine learning in the context of network security and proposes solutions to address these issues. The first part of the paper outlines the landscape of adversarial machine learning, elucidating the various types of attacks that can be leveraged against ML models used in network security. The second section delves into the unique challenges presented by adversarial attacks in the realm of network security. These challenges include the dynamic nature of network environments, the need for real-time decision-making, and the resource constraints often inherent in security applications. By providing a thorough examination of the challenges posed and proposing viable solutions, it contributes to the ongoing efforts to fortify ML-based security systems against the evolving landscape of cyber threats. The findings of this research have the potential to inform the development and deployment of more robust and resilient network security solutions in the face of adversarial machine learning attacks.